Os moradores de Belém e suas relações com a cidade: tessitura de uma cartografia comunicativa - KABUENGE, Nathan Nguangu (Universidade Federal do Pará, 2024)
A present thesis analyzed the narrative constructions that the residentes of Belém create about themselves, the other and Belém. Considering the imaginary constructions that are established among the residents of the capital of Pará, fear constitutes one of the tensions in the fabric of the narratives. The question was asked in the analysis: How does the cartography of Belém allow us to observe the communicative processes of constructing the self, the other and the city? The question instigated the search to find out how the residents of Belém understand themselves in a relationship between the self and the other. In contemporary times, understanding this I-Thou relationship is justified because this relationship has been configured as calculating, to the extent that it makes the other an It, and not the externalized self that is decisive in understanding human action. As a methodological approach, a communicative cartography was developed in order to weave together the meanings attributed by individuals to themselves and to others, as well as to the spaces they experience. Cartography was understood as a relationship of power, tensions and force in the negotiation of meanings and the control of space as a product of social practices and relationships. In this construction, 15 narrative interviews were conducted with residents of 14 neighborhoods in Belém, from January to October 2022. The analyzes of such interviews were inspired by the theoretical-methodological openings: Ricoeur's narrative-hermeneutics, and his explanations of the unfolding of mimesis I, II and III; Deleuze and Guattari's cartography; Buber's ontological dimension of the I-Thou relationship; and Lévinas' ethical dimension of the faceto-face relationship. From the interlocutors' stories about and from Belém, we identified how a general frame was formed, called the "affective frame", with ramifications in other frames: urban, socio-cultural and security. In the affective frame, residents map the city of Belém in an affective and personal way. In all the frames, Communicative experiences emerged that were categorized into three dimensions: a) in the city center - a strong relationship of communication as possibility or miscommunication; b) in the periphery, communication as dialogue; and c) in Belém as a whole - communication as a relationship of otherness. The results of the research pointed to a cartography of the relationships, affections, intensities, conflicts, disputes over meanings, resistance, territoriality, deterritoriality and reterritoriality, which the residentes of Belém live create daily to make the city a place of possibility, as this same place holds, at the same time, a feeling of security and danger, where there is wealth and poverty. Despite these problems, the residentes of Belém strive, through cultural manifestations, to vibrate together around the city.